Investigation of psychological traits in patients with chronic abdominal pain syndrome - A. A. Tokareva; M. Ye. Melnikov; O. S. Shubina; I. A. Nesina; Ye. I. Miguskina (Бюллетень сибирской медицины)
Subjects of the study were 100 chronic abdominal pain syndrome inpatients assigned to subgroups of different level of significance of psychological factors for the development of pain syndrome, different self-assessed pain level (utilizing visual analog scale), and different type of attitude towards disease (by the Bekhterev Institute Personality Inventory). Character and psychodynamic specialties were assessed in the aforementioned subgroups following to assignment. Proved by clinical and psychometric methods diagnosis of somatoform pain disorder was used as an indicator of high importance of psychological determinants. Differences between subgroups were assessed by the kit of questionnaires (Beck Depression Inventory, Spielberger Anxiety Scales, Wasserman Social Frustration Inventory, TAS, MCMI-III) and projective tests (Luscher and Szondi tests). Interference between psychosomatic and demographic characteristics within the sample, and accuracy of assigning subjects to subgroups were discussed. Interpretation of the acquired data with implications for psychotherapists was offered.